Molecular epidemiology of influenza, RSV, and other respiratory infections among children in Qatar: A six years report (2012–2017). (June 2020) - Al-Romaihi, Hamad E.; Smatti, Maria K.; Al-Khatib, Hebah A.; Coyle, Peter V.; Ganesan, Nandakumar; Nadeem, Shazia; Farag, Elmoubasher A.; Al Thani, Asmaa A.; Al Khal, Abdullatif; Al Ansari, Khalid M.; Al Maslamani, Muna A.; Yassine, Hadi M.
Highlights: Throughout a five years period, HRV, RSV, and influenza viruses were responsible for two-thirds of acute respiratory infections among children in Qatar. RSV, influenza, and HMPV circulated in winter, whereas HRV was highly active during other seasons. RSV is more prevalent among infants, while influenza circulates more among children above five years of age. Influenza–RSV co-infections are significantly associated with age. Gender-dependent differences affect infection rates. Abstract: Background: Studies on the etiology of respiratory infections among children in Qatar and surrounding countries are limited. Objectives: To describe the prevalence and seasonality of RSV, influenza, and other respiratory pathogens among children in Qatar. Methods: We retrospectively collected and analyzed data of 33, 404 children (<15 years) presented with influenza-like illness from 2012 to 2017. Results: At least one respiratory pathogen was detected in 26, 138 (78%) of patients. Together, human rhinoviruses (HRV), respiratory syncytial virus (RSV), and influenza viruses comprised nearly two-thirds of all cases, affecting 24%, 19.7%, and 18.5%, respectively. A prevalence of 5-10% was recorded for adenovirus, parainfluenza viruses (PIVs), human bocavirus (HboV), and human coronaviruses (HCoVs). Human metapneumovirus (HMPV), enteroviruses, M. pneumonia, and parechovirus had prevalences below 5%. While RSV, influenza, and HMPV exhibited strong seasonal activity in the winter, HRV was active during low RSV and influenza circulation. The burden of RSV exceeds that of influenza among young age groups, whereas influenza correlated positively with age. Further, HRV, adenovirus, influenza, and RSV infection rates varied significantly between male and females. Conclusion: This comprehensive multi-year study provides insights into the etiology of ILI among children in Qatar, which represents the Gulf region. Our results reinforce the significance of active surveillance of respiratory pathogens to improve infection prevention and control strategies, particularly among children.